2016
DOI: 10.1016/j.fertnstert.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology alters deoxyribonucleic acid methylation profiles in bloodspots of newborn infants

Abstract: Both infertility and ICSI alter DNA methylation at specific genomic loci, an effect that is mitigated to some extent by FET. The impact of assisted reproductive technology and/or fertility status on metastable epialleles in humans was uncovered. This study provides an expanded set of loci for future investigations on IVF populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 64 publications
(91 reference statements)
2
74
0
2
Order By: Relevance
“…A particular strength of this study is that the embryos in both IVF groups were transferred into physiologic hormonal environments, thus minimizing the confounding effects of superovulation on the endometrium. Several other studies have reported similar patterns in other genes related to growth, with frozen embryos yielding epigenetic patterns and gene expression more similar to natural conception (Estill et al, ; Ghosh, Coutifaris, Sapienza, & Mainigi, ). This suggests a potential mechanism of vitrification resulting in reversal of the epigenetic effects of superovulation on the oocyte, with consequentially larger babies.…”
Section: Proposed Mechanismsmentioning
confidence: 61%
“…A particular strength of this study is that the embryos in both IVF groups were transferred into physiologic hormonal environments, thus minimizing the confounding effects of superovulation on the endometrium. Several other studies have reported similar patterns in other genes related to growth, with frozen embryos yielding epigenetic patterns and gene expression more similar to natural conception (Estill et al, ; Ghosh, Coutifaris, Sapienza, & Mainigi, ). This suggests a potential mechanism of vitrification resulting in reversal of the epigenetic effects of superovulation on the oocyte, with consequentially larger babies.…”
Section: Proposed Mechanismsmentioning
confidence: 61%
“…It has been reported that global genomic methylation in vitrification groups is lower in mouse MII oocytes, two to eight cell embryos and blastocysts than in controls (Chen, Shi et al, ; Cheng et al, ; Liang et al, ; Yao et al, ). However, the methylation profiles of infants obtained through ICSI‐frozen (FET) and intrauterine insemination (IUI) methods are strikingly similar, and this finding was similar to our results (Estill et al, ). Thus, we infer that the methylation changes observed in the VET group and IVC group might be important for ART clinics.…”
Section: Discussionmentioning
confidence: 99%
“…They addressed several caveats of the IVF process including epigenetic erasure and reprogramming. However, in light of more recent evidence that IVF alters DNA methylation [26,27] and the expression of microRNAs in the fetal brain that regulate neuronal migration, differentiation and development [28], one should be cautious in interpreting IVF experiments with respect to epigenetic mechanisms mediating transgenerationally transmitted effects of paternal stress [see 22 for further discussion of this issue].…”
Section: Paternal Stress Influences Male Offspring Anxiety and Depresmentioning
confidence: 99%